Engaging Students in Chemistry and Physics with an Active Methodology - Ribau, Isabel (Advances in Social Sciences Research Journal, 2023)
Science, technology, engineering, and mathematics (STEM) play an important role in the global economy through technological innovation, creation, and problem-solving in this century. But it is difficult to capture students’ attention to it, and the loss of students in the STEM field hinders society's development, and Portugal is no exception. The students feel that this field is difficult, they feel disappointed as the academic outcomes are more difficult to obtain in the upper secondary, and they easily give up on this area and/or choose other fields. To mesmerize students in the science area and reinforce their positive emotions a project was elaborated based on flipped classrooms with a laboratory station model and started in September 2021. A study case was designed to perceive the impact of the laboratory station methodology and flipped classrooms on the motivation of upper-secondary science students. Self-response questionnaires were applied before and after an intervention phase where students had flipped classrooms and laboratory stations, experimental classes, during one school year. This research concludes that this teaching methodology allows students to maintain motivation throughout the school year. The teacher´s attitudes regarding school, learning and teaching processes, influence students and can trigger positive emotions concerning overcoming school difficulties and barriers they found during their learning journey. It is essential to disseminate these results, as they can help teachers to face the difficulties of engaging students in the learning process in the science field. As the limitation of this study is the small sample (26 students), this study will be replicated with new students in 10th grade and students who were part of this study will continue to be followed as this methodology will continue to be applied in 11grade.